Scientific literature reviews; Investigating analysis of turbine blade operational failure - Riki Effendi; Franka Hendra (Politeknik Negeri Lhokseumawe, 2023)
As a source of energy in industry and power plants, turbines must have reliability in operation.. One that affects the performance of the turnin is the condition of the blades. The multi-cycle fatigue experienced by the blades of compressors and turbines caused by dynamic stresses caused by the vibration and resonance of the blades in the engine operating time is a common type of failure. Over the past five decades, researchers have studied and investigated turbine blade failure. The main purpose of this article is to provide a brief overview of recent studies on turbine blade failure. The author only focuses on describing some of the failure methodologies used in various studies to investigate turbine blades. This article discusses each of these factors in more detail